AUDIT RISK ANALYSIS IN ADJUSTMENT OF AUDIT PROCESS IN INDONESIA - Riska Franita (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2025)
This research focuses on the results of adjustment audits in Indonesia using secondary data. The greater the audit risk, the greater the adjustments made by the auditor. Auditors must be able to understand the client's business in depth, conduct initial risk assessments, establish materiality, and develop risk-based audit plans. have knowledge in AI, and prepare a competent team